(untitled) (Educational Knowledge, 2015)
The academic performance of newly enrolled students in the second semester of 2013 in Bachelor’s and Engineering programs at the Multidisciplinary Faculty of Ilobasco, Catholic University of El Salvador, was studied. Passing and failing rates were established through a comparison by major, gender, and high school. A list of courses taught during the semester, along with their respective pass and fail rates, is also presented. The data was obtained using grades provided by the University’s academic records office. Students who failed courses were identified and interviewed in writing to determine the main reasons for this. Overall, academic performance increased by 27.4% for male students and by 3.9% for female students during the semester. Furthermore, 31.3% of the students failed at least one course.